The next great war? the roots of World War I and the risk of U.S.-China conflict /cedited by Richard N.Rosecrance and Steven E. Miller - Rosecrance, Richard N.; Miller, Steven E. (Belfer Center studies in international security, 2015)
A century ago, Europe's diplomats mismanaged the crisis triggered by the murder of Archduke Franz Ferdinand of Austria, plunging the continent into World War I which killed millions, toppled dynasties, and destroyed empires. Today as the hundredth anniversary of the Great War prompts renewed debate about the war's causes, scholars and policy-makers are also considering the parallels between the present international system and the system of 1914. Are China and the United States fated to follow in the footsteps of previous Great Power rivals? Will today's alliances drag countries into tomorrow's wars? This book concludes that only a deep understanding of the causes of previous war and early action to bring great powers together would enable the United States and China to avoid a great war